Management of Guidance and Counseling on Learning Discipline - Muhammad Syauqi Mubarok (International Journal of Islamic Khazanah, 2020)
This article aims to examine and describe the influence of guidance and counseling management on learning discipline. The method used in this research is descriptive analysis method using survey techniques. Data collection techniques that used are documentation studies and field studies. Moreover, the data analysis technique that has been used to answer the research hypothesis is statistical analysis with a path analysis model. The location of the study was at the Ciledug Vocational High School Al-Musaddadiyah Garut, with 85 respondents taking part in the survey. The results of the discussion show that guidance and counseling management has a positive and significant effect on the discipline of learning